PENGARUH GOOD CORPORATE GOVERNANCE, FIRM SIZE, STRUKTUR MODAL TERHADAP KINERJA KEUANGAN PADA PERUSAHAAN ANEKA INDUSTRI, INDUSTRI DASAR DAN KIMIA DI BEI PERIODE 2014-2017 - Napitupulu, Reizkey; Kristina; Ndruru, Rismawati; Waruwu, Yanuari; Sipahutar, Tetty Tiurma Uli (KRISNA: Kumpulan Riset Akuntansi, 2021)
This research is discussed to assess Good Corporate Governance (GCG) of Company Size, Capital Structure of Return on Investment in Various Industrial, Basic and Chemical Companies. Sampling using purposive sampling produced as many as 38 sample companies from a population of 110 companies with a total of 168 observations of the analysis unit. The results of the study stated that Good Corporate Governance (GCG), Company Size, and capital structure simultaneously had a significant and significant effect on return on investment (ROI) in various industries, basic industries, and chemicals on the Indonesia Stock Exchange. partially Good corporate governance has no effect and no significant effect on investment returns, company size partially has a negative and insignificant effect on investment returns and capital structure partially has a negative and significant effect on investment returns in companies in various industries, basic industries, and chemicals on the Indonesia Stock Exchange.